The Jäger Report: An Invaluable Source of the Efficiency of Einsatzkommando 3 (Einsatzgruppe A) that Illustrates the Annihilation by Bullets of Jewish Men, Women, and Children in Lithuania - Tejeda Barros, Antonia (Historiografías, 2025)
The Einsatzgruppen massacres mark a turning point in the mass extermination of Jewish men, women, and children during the Shoah. The Jäger report is one of the most detailed sources of the Einsatzgruppen massacres; it thoroughly details the killings of 137,448 victims (the total number of victims given in the report is inaccurate), of whom 135,392 are Jewish victims and 2,056 are non-Jewish victims. The disproportion between Jewish victims (98.5 percent) and non-Jewish victims (1.5 percent) in the report is gigantic. The massacres of the Jäger report were carried out by Einsatzkommando 3 of Einsatzgruppe A (with the enthusiastic collaboration of the Lithuanian auxiliary police), mainly in Lithuania, from July 4, 1941, to November 29, 1941, solely by bullets. Although there are in fact two Jäger reports (September 10 and December 1, 1941), in the present paper I focus on the later one, known as ‘the’ Jäger report. After briefly introducing Operation Barbarossa and describing the structure of the four Einsatzgruppen, I analyze the Jäger report, while emphasizing the high number of Jewish victims (who were slaughtered only because they were Jewish) versus the much lower number of non-Jewish victims (all of whom, except for one Roma/Sinti child and 48 children with physical, psychiatric, and intellectual disabilities –so-called ‘Geisteskranke’, do not include children). I argue that separating Jewish victims from non-Jewish victims is paramount to a serious research of both the Einsatzgruppen and the Shoah. Keywords Jäger report, Einsatzgruppen, Einsatzgruppe A, Einsatzkommando 3, Jewish victims, Shoah